PRARANCANGAN PABRIK KIMIA METIL ETIL KETON DARI 2-BUTANOL KAPASITAS 60.000 TON/TAHUN - , NINA ANGGITA WARDANI; , Dr. Ir. Sarto, M. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Methyl chloroform or 1,1,1-trichloroethane is made with hydrochlorination process from 1,1-dichloroethane and chlorine without using catalyst in fixed bed multitubes reactor. The formation of 1,1-dichloroethane made from chlorination process of vinyl chloride monomer and HCl in gas phase with FeCl3 catalyst in fixed bed multitubes reactor. This reaction is exothermic and occurs in temperature 127- 142Â°C and pressure 2,9-3,5 atm. The temperature inside reactor is to be maintained stable so that coolant in the form of dowtherm is needed. The dowtherm used is type- T. Reactor products are separated using distillation column with commercial product specification is 1,1,1-trichloroethane of 99.5% purity. 1,1,1-trichloroethane plant is designed for 50,000 ton/year capacity. Raw materials needed are vinyl chloride monomer 12,387,621 kg/year, HCl 10,276,099 kg/year chlorine 220,451,695 kg/year, and FeCl3 7,612,470 kg/year. Plant is designed to be built in Cilegon, Banten with 10 Ha area needed and 247 labors needed. Utilities needed are 575,190 m3/year water, 2000 kVA electricity, 150,000 kg/year dowtherm T, 894,960 m3/year compressed air, and 371,575 kg/year fuel gas. From economic evaluation are obtained $ 147,721,679.43 + Rp 261,560,987,514 fixed capital, $ 33,332,957.7 + Rp 13,833,101,206 working capital, $ 94,825,448.72 + Rp 78,705,575,828 manufacturing cost, $ 39,061,980.63 + Rp 6,498,739,320 general expense, Rp 221,413,500 sales, Rp 85,204,369,148 + $ 133,887,429.35 total cost. Profit after tax is Rp 351,265,133,340